MINDFULNESS AND INTERPRETIVE OUTCOME: A CASE OF GEORGE TOWN, PENANG, WORLD HERITAGE CITY - Tan Poh Ling; Md Noor, Shuhaida; Hasrina Mustafa (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The primary objective of this study is to further understand the concept of mindfulness and its contribution towards interpretation at the heritage sites. Mindfulness refers to psychological awareness based on experiencing the current environment by steering the careful attention through a non-critical state. Past research works have suggested that mindfulness is capable to contribute in creating effective interpretation among visitors. Although mindfulness has been acknowledged as important, there are gaps in understanding mindfulness and its contribution towards interpretation. The current research focuses on examining the contribution of mindfulness towards interpretation. This research is conducted in Penang, a destination listed under the UNESCO World Heritage. A self-administered questionnaire was prepared with 390 usable responses from both local and international tourists were gathered to empirically test the measurement and structural model by using Partial Least Square path modelling approach. The results illustrate the significant positive direct effects and path coefficients. Likewise, significant relationship exists between mindfulness and interpretation. Above all, this research contributes to the mindfulness literature and provides evidence on its contribution towards interpretation.